Kemampuan Guru Tersertifikasi dalam Perancangan dan Penerapan Pembelajaran (Studi Multisitus Pada SMK Negeri Kota Palu) - Syafruddin (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2017)
The purpose of this study was to describe: (1) the ability of a certified teacher in learning design; (2) the ability of certified teachers in implementing learning; and (3) barriers to certified teachers in the design and implementation of learning. The research location is public vocational high schools in Palu City. The approach used in this research is descriptive qualitative with a multisite case study design. Data collection methods / techniques, namely: interview / self-assessment rubric, observation, and document content analysis. The data analysis used the interactive triangulation model technique. The data sources are certified teachers and documentation materials relevant to the research objectives. The results of the study: (1) not all certified teachers have optimal abilities in learning design; (2) not all certified teachers have optimal abilities in the application of learning; and (3) the obstacles for certified teachers in the design and implementation of learning are technical and non-technical obstacles. Technical barriers relate to aspects of skills possessed by certified teachers. Meanwhile, non-technical barriers are limitations: aspects of knowledge, attitudes, time allocation, learning facilities and infrastructure in carrying out professional tasks.